Anti-migration long-life light conversion adhesive film as well as preparation method and application thereof

By setting up an anti-migration layer in the photoconverting adhesive film and adding inorganic nanopowders for electron beam irradiation pre-crosslinking, the problem of incomplete migration of the photoconverting additive and ultraviolet light conversion is solved, and the long life of the film is achieved and High efficiency performance of photovoltaic modules.

CN119410296AInactive Publication Date: 2025-02-11ZHEJIANG SINOPONT TECH

Patent Information

Application Number
CN202411978568.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the use of the existing optical conversion adhesive film, there are problems such as the migration of the optical conversion additive, resulting in functional attenuation, incomplete UV conversion, and easy failure of the optical conversion agent, which affects the long life and power performance of the photovoltaic module.

Method used

A migration-proof layer is provided between the light-transforming layer and the UV cut-off layer, and inorganic nanopowders are added and electron beam irradiation is pre-crosslinked to block the migration channel of the auxiliary agent and prevent the mutual interaction between the light-transforming agent and the ultraviolet absorber. migrate.

Benefits of technology

It effectively prevents the migration of light-transforming agents and ultraviolet absorbers, extends the service life of the adhesive film, and improves the UV resistance and overall power performance of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410296A_ABST
    Figure CN119410296A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photovoltaic adhesive films, and discloses an anti-migration long-service-life light conversion adhesive film and a preparation method and application thereof.The anti-migration long-service-life light conversion adhesive film comprises a light conversion layer, an anti-migration layer and a UV cut-off layer which are sequentially arranged in an attached mode; the raw materials of the light conversion layer comprise first matrix resin and a light conversion agent; the raw materials of the anti-migration layer comprise second matrix resin and inorganic nano powder; the particle size D50 of the inorganic nano powder is 1-200nm, and the mass of the inorganic nano powder is 0.01-0.5% of the total mass of the anti-migration layer; the anti-migration layer is pre-crosslinked through electron beam irradiation; the raw materials of the UV cut-off layer comprise third matrix resin and an ultraviolet absorbent. The anti-migration layer added with the inorganic nano powder and pre-crosslinked through electron beam irradiation is arranged between the light conversion layer and the UV cut-off layer, the free volume of a crosslinked polymer can be effectively reduced by adding the inorganic nano powder and carrying out electron beam irradiation pre-crosslinking, and a migration channel of an auxiliary agent is blocked; mutual migration of the light conversion agent and the ultraviolet absorbent is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic adhesive films, and in particular to an anti-migration long-life light-conversion adhesive film and a preparation method and application thereof. Background Art

[0002] With the continuous development of photovoltaic cell technology, heterojunction (HJT) cells have attracted much attention due to their simple process and excellent photoelectric conversion efficiency. However, this type of cell usually uses amorphous or microcrystalline silicon technology, and the Si-H groups on the surface are easily damaged by ultraviolet radiation, resulting in defects and causing component power attenuation.

[0003] There are two main technical solutions to this problem on the market, using UV cut-off film and UV conversion film. UV cut-off film can absorb ultraviolet light and dissipate it in the form of heat, thereby achieving the purpose of protecting the cells, but this solution will weaken the utilization rate of photoelectrons by the cells and reduce the overall power of photovoltaic modules. UV conversion film mainly adds light conversion additives to conventional high-transmittance film to convert ultraviolet light that is harmful to the cells into visible light with higher photoelectric conversion efficiency, taking into account the functions of protecting the cells and increasing the power of the module.

[0004] However, the light-converting adhesive films currently used in the market generally have the following problems: 1) The migration of the light-converting agent causes the light-converting function to decay; 2) The ultraviolet light conversion is not complete, and part of the ultraviolet light reaches the battery cell and causes damage; 3) The light-converting agent is easy to fail, and the battery is directly exposed to the ultraviolet environment, damaging the battery cell. In response to the above problems, there is a method in the prior art of adding a cut-off agent to the light-converting adhesive film. The cut-off agent and the light-converting agent are used at the same time. Once the light-converting agent fails, the cut-off agent can still protect the battery cell from damage by ultraviolet rays; but in this method, the cut-off agent and the light-converting agent will interact with each other and weaken the light-converting effect. The light-converting film disclosed in patent CN115044325A is set as a two-layer structure, the outer layer is a light-converting adhesive film, and the inner layer is an ultraviolet cut-off adhesive film. The two layers perform their own functions. Once the light-converting layer fails, the cut-off layer can still protect the battery cell; but the two additives in this method will migrate to each other, resulting in the same problem as the simultaneous use of the cut-off agent and the light-converting agent. Patent CN116766721A discloses a three-layer structure of a light-converting film, with an outer layer of light-converting EVA, a middle polymer barrier layer that can effectively slow down the mutual migration of the light-converting agent and the ultraviolet shielding agent, and an inner layer of ultraviolet cutoff layer EVA. However, the barrier layer of this method uses ester polymers, olefin polymers, and acrylic polymers with a melting point greater than 200°C. These polymers have high melting points and good barrier properties, and can solve the problem of auxiliary agent migration to a certain extent. However, these three types of resins belong to engineering plastics, and their mechanical properties such as modulus, strength, and hardness are relatively high, which will increase the risk of cell splitting, and therefore are not suitable for photovoltaic modules; secondly, due to the high melting point, the barrier layer composed of these three types of polymers will not melt during the lamination of the module, which will result in the formation of a clear interface after pressing, increasing the risk of module reliability failure; finally, compared with conventional photovoltaic encapsulation film materials, these three types of materials are relatively expensive, and cannot be used on a large scale for the photovoltaic industry, which has extremely strict cost requirements. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned problems existing in the light-converting adhesive film in the prior art, and provides an anti-migration long-life light-converting adhesive film and a preparation method and application thereof. An anti-migration layer to which inorganic nanopowder is added and pre-crosslinked by electron beam irradiation is arranged between the light-converting layer and the UV cutoff layer. The addition of inorganic nanopowder and the pre-crosslinking by electron beam irradiation can effectively reduce the free volume of the cross-linked polymer, block the migration channel of the auxiliary agent, and effectively prevent the mutual migration of the light-converting agent and the ultraviolet absorber.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides an anti-migration long-life light-converting adhesive film, comprising a light-converting layer, an anti-migration layer and a UV cut-off layer which are laminated in sequence; The raw materials of the light conversion layer include a first base resin and a light conversion agent; The raw materials of the anti-migration layer include a second matrix resin and an inorganic nano powder; the particle size D50 of the inorganic nano powder is 1-200 nm, and the mass of the inorganic nano powder is 0.01-0.5% of the total mass of the anti-migration layer; the thickness of the anti-migration layer is 15-45% of the total thickness of the anti-migration long-life light-converting adhesive film; the anti-migration layer is pre-crosslinked by electron beam irradiation; The raw materials of the UV cut-off layer include a third base resin and an ultraviolet absorber.

[0007] In the light-converting adhesive film of the present invention, the outer layer is a light-converting layer with a light-converting agent added, which can convert ultraviolet light that is harmful to the battery cell into visible light with higher photoelectric conversion efficiency, taking into account the functions of protecting the battery cell and improving the power of the component; the inner layer is a UV cut-off layer with an ultraviolet absorber added, which can absorb ultraviolet light and dissipate it in the form of heat, thereby achieving the purpose of protecting the battery cell; even if the light-converting layer fails, the UV cut-off layer can still protect the battery cell. At the same time, the present invention sets an anti-migration layer with inorganic nanopowder added between the light-converting layer and the UV cut-off layer. The size of the inorganic nanopowder is smaller than the wavelength of light that can be used by solar cells, and a small amount of addition will not affect the overall light transmittance of the adhesive film. In addition, the addition of inorganic nanopowder can effectively reduce the free volume of the cross-linked polymer, block the migration channel of the auxiliary agent, effectively prevent the mutual migration of the light-converting agent and the ultraviolet absorber, avoid the interaction between the two, and weaken the light-converting effect.

[0008] In addition, the anti-migration layer of the present invention is pre-crosslinked by electron beam irradiation. In conventional photovoltaic film lamination heat crosslinking, free radicals generated by the decomposition of organic peroxide initiators are usually used as active sites. The crosslinking density and the uniformity of the crosslinking reaction are completely dependent on the amount of initiator used and the uniformity of mixing with particles. When the amount of initiator is too large, there are too many residual additives, which causes component reliability problems; when the amount is small, the uniformity of mixing is difficult to ensure, resulting in uneven crosslinking in the film, low crosslinking density, and high free volume ratio, which increases the possibility of additive migration. The present invention adopts electron beam irradiation pre-crosslinking, and each electron is equivalent to an active site. The number, energy and distribution characteristics of electrons can be freely adjusted within the functional range of the electron accelerator. In this case, the crosslinking density (number of crosslinking points) of the film can be effectively guaranteed, thereby reducing the permeability of the film to the additive. After pre-crosslinking by electron beam irradiation, the inorganic nanoparticles are firmly fixed inside the film, and there will be no migration or precipitation of inorganic nanopowders, thereby improving the service life of the film.

[0009] Preferably, the inorganic nano powder is selected from one or more of nano calcium carbonate, nano silicon dioxide, nano talc, nano wollastonite, nano titanium dioxide, nano barium sulfate, nano kaolin, nano montmorillonite, nano aluminum hydroxide, nano zinc oxide, and nano aluminum oxide.

[0010] Preferably, the total thickness of the anti-migration long-life light-converting adhesive film is 500-1400 μm; the thickness of the light-converting layer is 200-600 μm; the thickness of the anti-migration layer is 100-200 μm; and the thickness of the UV cutoff layer is 200-600 μm.

[0011] Preferably, the mass of the light conversion agent is 0.02-0.6% of the total mass of the light conversion layer; the mass of the ultraviolet absorber is 0.02-1.0% of the total mass of the UV cutoff layer.

[0012] Preferably, the first matrix resin is selected from one or more of POE, EVA, and PVB; the second matrix resin is selected from one or more of EVA, POE, TPO, PVB, and silica gel; and the third matrix resin is selected from one or more of POE, EVA, and PVB.

[0013] Preferably, the light conversion layer, the anti-migration layer and the UV cut-off layer further include one or more of a cross-linking agent, a co-cross-linking agent, a silane coupling agent, a photoinitiator, an antioxidant and a light stabilizer.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned anti-migration long-life light-conversion adhesive film, comprising the following steps: (1) Mixing the raw materials of the anti-migration layer in proportion and casting the mixture to form a film, and cooling and forming the film to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain a pre-crosslinked anti-migration layer; (3) preparing a light conversion layer and a UV cutoff layer by a casting method, and after cooling and forming, laminating the obtained pre-crosslinked anti-migration layer between the light conversion layer and the UV cutoff layer by roller pressing, thereby obtaining the anti-migration long-life light conversion adhesive film.

[0015] Preferably, the pre-crosslinking degree of the pre-crosslinked anti-migration layer obtained in step (2) is 20-80%.

[0016] Preferably, in step (3), the temperature during roller pressing is 50-110° C. and the pressure is 0.1-10.0 MPa.

[0017] In the third aspect, the present invention provides an application of the above-mentioned anti-migration and long-life light conversion adhesive film in a photovoltaic module, wherein the photovoltaic module includes a solar cell, and the two sides of the solar cell are respectively bonded with the anti-migration and long-life light conversion adhesive film; the UV cutoff layer of the anti-migration and long-life light conversion adhesive film is bonded to the solar cell.

[0018] Therefore, the present invention has the following beneficial effects: (1) Adding inorganic nanopowders to the anti-migration layer can reduce the free volume of the film, block the migration path of the light conversion agent and the ultraviolet absorber, avoid the interaction between the two, and weaken the light conversion effect; (2) Radiation pre-crosslinking improves the crosslinking density and crosslinking uniformity of the anti-migration layer, which is beneficial to prevent the migration of light conversion agents and ultraviolet absorbers and the migration or precipitation of inorganic nanopowders, thereby increasing the service life of the film; (3) The three-layer film structure is formed by cold pressing with two rollers. The steps are simple and the film performance is stable and controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic structural diagram of the anti-migration and long-life light-converting adhesive film of the present invention.

[0020] Figure 2 The present invention is a flow chart for preparing the anti-migration and long-life light-converting adhesive film.

[0021] Figure 3 It is a schematic diagram of the application of the anti-migration and long-life light-converting adhesive film of the present invention in a photovoltaic module.

[0022] In the figure: a long-life light-converting adhesive film 1, a light-converting layer 1-1, an anti-migration layer 1-2, a UV cutoff layer 1-3, a solar cell sheet 2, a casting machine 3, a pair of rollers 4, and a winding device 5. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0024] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0025] Overall embodiment: like Figure 1 As shown, an anti-migration long-life light-converting adhesive film 1 comprises a light-converting layer 1-1, an anti-migration layer 1-2 and a UV cut-off layer 1-3 which are laminated in sequence; The raw materials of the light conversion layer include a first base resin and a light conversion agent; The raw materials of the anti-migration layer include a second matrix resin and an inorganic nano powder; the particle size D50 of the inorganic nano powder is 1-200 nm, and the mass of the inorganic nano powder is 0.01-0.5% of the total mass of the anti-migration layer; the thickness of the anti-migration layer is 15-45% of the total thickness of the anti-migration long-life light-converting adhesive film; the anti-migration layer is pre-crosslinked by electron beam irradiation; The raw materials of the UV cut-off layer include a third base resin and an ultraviolet absorber.

[0026] As a specific implementation, the inorganic nanopowder is selected from one or more of nano calcium carbonate, nano magnesium hydroxide, nano silicon dioxide, nano talc, nano wollastonite, nano titanium dioxide, nano barium sulfate, nano kaolin, nano montmorillonite, nano aluminum hydroxide, nano zinc oxide, and nano aluminum oxide.

[0027] As a specific implementation, the total thickness of the anti-migration long-life light-converting adhesive film is 500-1400 μm; the thickness of the light-converting layer is 200-600 μm; the thickness of the anti-migration layer is 100-200 μm; and the thickness of the UV cutoff layer is 200-600 μm.

[0028] As a specific implementation manner, the mass of the light conversion agent is 0.02-0.6% of the total mass of the light conversion layer; the mass of the ultraviolet absorber is 0.02-1.0% of the total mass of the UV cutoff layer.

[0029] As a specific implementation, the light conversion agent is selected from one or more of powdered inorganic metal oxides, organic molecules, semiconductor quantum dots and rare earth complex light conversion agents.

[0030] As a specific embodiment, the ultraviolet absorber is selected from one or more of UV-9, UV-531, UV-320, UV-327, UV1577, UV6198, UV234, UV312, UV328, and UV3480.

[0031] As a specific implementation, the first matrix resin is selected from one or more of POE, EVA, and PVB; the second matrix resin is selected from one or more of EVA, POE, TPO, PVB, and silicone; and the third matrix resin is selected from one or more of POE, EVA, and PVB.

[0032] As a specific implementation, the light conversion layer, the anti-migration layer and the UV cut-off layer further include one or more of a cross-linking agent, a co-cross-linking agent, a silane coupling agent, a photoinitiator, an antioxidant and a light stabilizer.

[0033] As a specific embodiment, the photoinitiator is selected from one or more of benzoin and its derivatives, benzil, alkyl phenones, acyl phosphorus oxides, benzophenones, thioxanthones, diaryl iodonium salts, triaryl iodonium salts, alkyl iodonium salts, and isopropyl ferrocenium hexafluorophosphate.

[0034] As a specific embodiment, the cross-linking agent is one or more of di-tert-butyl peroxide, tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxy 2-ethylhexyl carbonate, and isopropylbenzene peroxide.

[0035] As a specific embodiment, the auxiliary cross-linking agent is one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, glycerol trihydroxypropyl ether triacrylate, trimethylolpropane diallyl ether, triallyl cyanurate, trimethallyl isocyanate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, N,N'-methylenebisacrylamide, trivinylmethoxysilane, trivinylethoxysilane, allyl triethoxysilane, and tetramethyltetravinylcyclotetrasiloxane.

[0036] As a specific embodiment, the silane coupling agent is one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxide tert-butyl silane, vinyl triacetoxysilane, vinyl tri(β-methoxyethoxy) silane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, and 3-aminopropyl trimethylsilane.

[0037] As a specific embodiment, the antioxidant is one or more of p-phenylenediamine, dihydroquinoline, 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, bis(3,5-di-tert-butyl-4-hydroxyphenyl) sulfide, thiodipropionic acid diester, and didodecanol ester.

[0038] As a specific embodiment, the light stabilizer is one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 4-(methyl)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, 3,5-di-tert-butyl-4-hydroxy-benzoic acid hexadecyl ester, and tris(1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite.

[0039] The preparation process of the above anti-migration long-life light-converting adhesive film is as follows: Figure 2 As shown in , the method includes the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer 1-2; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain a pre-crosslinked anti-migration layer; (3) The light-conversion layer 1-1 and the UV cutoff layer 1-3 are prepared respectively by two casting machines 3. After cooling and forming, the obtained pre-crosslinked anti-migration layer is pressed between the light-conversion layer and the UV cutoff layer by a pair of rollers 4 to obtain the anti-migration long-life light-conversion adhesive film 1, which is then rolled up by a winding device 5 for standby use.

[0040] As a specific implementation manner, the pre-crosslinking degree of the pre-crosslinked anti-migration layer obtained in step (2) is 20-80%.

[0041] As a specific implementation, in step (3), the temperature during roller pressing is 50-110° C., and the pressure is 0.1-10.0 MPa.

[0042] The application of the above anti-migration long-life light conversion film in photovoltaic modules, such as Figure 3 As shown in , the photovoltaic module includes a solar cell 2, and the two sides of the solar cell are respectively adhered with the anti-migration long-life light conversion adhesive film 1; the UV cutoff layers 1-3 of the anti-migration long-life light conversion adhesive film are adhered to the solar cell.

[0043] Embodiment 1: An anti-migration long-life light-converting adhesive film, with a thickness of 850 μm, comprising a light-converting layer with a thickness of 350 μm, an anti-migration layer with a thickness of 150 μm and a UV cut-off layer with a thickness of 350 μm which are laminated in sequence; In parts by weight, the raw materials of the light-converting layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12 g / 10 min), 0.2 parts of commercial rare earth complex light-converting powder, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.5 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.15 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.1 parts of nano calcium carbonate (D50=80 nm), 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.2 parts of vinyl triethoxysilane, 0.2 parts of isopropyl ferrocenium hexafluorophosphate, 0.1 parts of p-phenylenediamine, 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the UV cutoff layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.2 parts of ultraviolet absorber UV-320, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.8 parts of triallyl isocyanurate, 0.5 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid.

[0044] The method for preparing the above-mentioned anti-migration long-life light-converting adhesive film comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain an anti-migration layer with a pre-crosslinking degree of 52.2%; (3) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained pre-crosslinked anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use; the temperature during the roller lamination is 80°C and the pressure is 0.4 MPa.

[0045] Embodiment 2: An anti-migration long-life light-converting adhesive film with a thickness of 800 μm, comprising a light-converting layer with a thickness of 350 μm, an anti-migration layer with a thickness of 100 μm and a UV cut-off layer with a thickness of 350 μm which are laminated in sequence; In parts by weight, the raw materials of the light-converting layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12 g / 10 min), 0.2 parts of commercial rare earth complex light-converting powder, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.5 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12g / 10min), 0.1 parts of nano-silica (D50=100nm), 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.1 parts of vinyl triethoxysilane, 0.2 parts of isopropyl ferrocenium hexafluorophosphate, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the UV cutoff layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.2 parts of UV absorber UV-320, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.5 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid.

[0046] The method for preparing the above-mentioned anti-migration long-life light-converting adhesive film comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain an anti-migration layer with a pre-crosslinking degree of 51.78%; (3) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained pre-crosslinked anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use; the temperature during the roller lamination is 80°C and the pressure is 0.4 MPa.

[0047] Embodiment 3: An anti-migration long-life light-converting adhesive film with a thickness of 850 μm, comprising a light-converting layer with a thickness of 350 μm, an anti-migration layer with a thickness of 150 μm and a UV cut-off layer with a thickness of 350 μm which are laminated in sequence; In parts by weight, the raw materials of the light-converting layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12 g / 10 min), 0.2 parts of commercial rare earth complex light-converting powder, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.4 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.1 parts of nano magnesium hydroxide (D50=50nm), 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.1 parts of vinyl triethoxysilane, 0.2 parts of isopropyl ferrocenium hexafluorophosphate, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The raw materials of the UV cutoff layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.4 parts of ultraviolet absorber UV-320, 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.4 parts of vinyl triethoxysilane, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid.

[0048] The method for preparing the above-mentioned anti-migration long-life light-converting adhesive film comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain an anti-migration layer with a pre-crosslinking degree of 53.01%; (3) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained pre-crosslinked anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use; the temperature during the roller lamination is 80°C and the pressure is 0.4 MPa.

[0049] Embodiment 4: An anti-migration long-life light-converting adhesive film with a thickness of 900 μm, comprising a light-converting layer with a thickness of 350 μm, an anti-migration layer with a thickness of 200 μm and a UV cut-off layer with a thickness of 350 μm which are laminated in sequence; In parts by weight, the raw materials of the light conversion layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12g / 10min), 0.2 parts of commercially available benzotriazole derivative organic light conversion agent, 0.7 parts of isopropyl peroxide, 0.7 parts of trimethylolpropane trimethacrylate, 0.4 parts of γ-aminopropyl triethoxysilane, 0.1 parts of dihydroquinoline, 0.1 parts of tris(1,2,2,6,6-pentamethyl-4-piperidinyl)phosphite; The raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.1 parts of nano calcium carbonate (D50=80nm), 0.7 parts of cumene peroxide, 0.7 parts of trimethylolpropane trimethacrylate, 0.1 parts of γ-aminopropyl triethoxysilane, 0.2 parts of cumene ferrocenium hexafluorophosphate, 0.1 parts of dihydroquinoline, 0.1 parts of tris(1,2,2,6,6-pentamethyl-4-piperidinyl)phosphite; The raw materials of the UV cutoff layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12g / 10min), 0.6 parts of UV absorber UV-320, 0.7 parts of isopropyl peroxide, 0.7 parts of trimethylolpropane trimethacrylate, 0.45 parts of γ-aminopropyl triethoxysilane, 0.1 parts of dihydroquinoline, and 0.1 parts of tris(1,2,2,6,6-pentamethyl-4-piperidinyl)phosphite.

[0050] The method for preparing the above-mentioned anti-migration long-life light-converting adhesive film comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain an anti-migration layer with a pre-crosslinking degree of 52.6%; (3) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained pre-crosslinked anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use; the temperature during the roller lamination is 80°C and the pressure is 0.4 MPa.

[0051] Embodiment 5: An anti-migration long-life light-converting adhesive film with a thickness of 900 μm, comprising a light-converting layer with a thickness of 400 μm, an anti-migration layer with a thickness of 150 μm and a UV cut-off layer with a thickness of 350 μm which are laminated in sequence; In parts by weight, the raw materials of the light-converting layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12 g / 10 min), 0.25 parts of commercially available benzotriazole derivative organic light-converting agent, 0.7 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.7 parts of glycerol trihydroxypropyl ether triacrylate, 0.45 parts of vinyl trimethoxysilane, 0.1 parts of 2,6-di-tert-butyl-4-methylphenol, and 0.1 parts of tris(1,2,2,6,6-pentamethyl-4-piperidinyl)phosphite; The raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.1 parts of nano calcium carbonate (D50=80nm), 0.7 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.7 parts of glycerol trihydroxypropyl ether triacrylate, 0.1 parts of vinyl trimethoxysilane, 0.2 parts of isopropyl ferrocenium hexafluorophosphate, 0.1 parts of 2,6-di-tert-butyl-4-methylphenol, 0.1 parts of tris (1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite; The raw materials of the UV cutoff layer include: 95 parts of POE resin (8411 Dow, USA, melt index is 12g / 10min), 0.6 parts of ultraviolet absorber UV-320, 0.7 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.7 parts of glycerol trihydroxypropyl ether triacrylate, 0.4 parts of vinyl trimethoxysilane, 0.1 parts of 2,6-di-tert-butyl-4-methylphenol, and 0.1 parts of tris(1,2,2,6,6-pentamethyl-4-piperidinyl)phosphite.

[0052] The method for preparing the above-mentioned anti-migration long-life light-converting adhesive film comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain an anti-migration layer with a pre-crosslinking degree of 54.1%; (3) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained pre-crosslinked anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use; the temperature during the roller lamination is 80° C. and the pressure is 0.4 MPa.

[0053] Comparative Example 1 (no anti-migration layer): The difference between Comparative Example 1 and Example 1 is that no anti-migration layer is arranged between the light conversion layer and the UV cutoff layer, and the raw materials, dosage and thickness of the light conversion layer and the UV cutoff layer are the same as those in Example 1; its preparation method comprises the following steps: respectively mixing the raw materials of the light conversion layer and the UV cutoff layer in proportion, respectively preparing the light conversion layer and the UV cutoff layer by two casting machines, and after cooling and forming, laminating the obtained light conversion layer and the UV cutoff layer by rollers to obtain a light conversion adhesive film, which is rolled up by a winding device for standby use; the temperature and pressure during roller lamination are the same as those in Example 1.

[0054] Comparative Example 2 (the anti-migration layer is not pre-crosslinked by electron beam irradiation): The raw materials, dosage and thickness of the light transfer layer, the anti-migration layer and the UV cut-off layer in Comparative Example 2 are the same as those in Example 1; and the preparation method thereof comprises the following steps: (1) mixing the raw materials of the anti-migration layer in proportion and casting the mixture into a film, and cooling the mixture to obtain the anti-migration layer; (2) The raw materials of the light conversion layer and the UV cutoff layer are mixed in proportion, and the light conversion layer and the UV cutoff layer are prepared respectively by two casting machines. After cooling and forming, the obtained anti-migration layer is laminated between the light conversion layer and the UV cutoff layer by a pair of rollers to obtain the anti-migration long-life light conversion adhesive film, which is rolled up by a winding device and set aside for use. The temperature and pressure during the roller lamination are the same as those in Example 1.

[0055] Comparative Example 3 (the particle size of the inorganic powder is too large): The difference between Comparative Example 3 and Example 1 is that calcium carbonate with D50=2.5 ​​μm is used in the anti-migration layer, and the rest is the same as in Example 1.

[0056] Comparative Example 4 (the amount of inorganic nanopowder added exceeds 0.5%): The difference between Comparative Example 4 and Example 1 is that the raw materials of the anti-migration layer include: 95 parts of POE resin (8411 Dow, USA, melt index of 12g / 10min), 0.6 parts of nano calcium carbonate (D50=80 nm), 0.7 parts of tert-butyl peroxyisopropyl carbonate, 0.7 parts of triallyl isocyanurate, 0.2 parts of vinyl triethoxysilane, 0.2 parts of isopropyl ferrocenium hexafluorophosphate, 0.1 parts of p-phenylenediamine, and 0.1 parts of bis-2,2,6,6-tetramethylpiperidinol sebacic acid; The rest are the same as in Example 1.

[0057] Comparative Example 5 (anti-migration layer is too thick): The difference between Comparative Example 5 and Example 1 is that the thickness of the anti-migration layer is 300 μm, and the rest is the same as that in Example 1.

[0058] The anti-migration and long-life light-converting adhesive films prepared in the above embodiments and comparative examples were tested for transmittance according to GB / T29848-2018; the components made by combining the light-converting adhesive films prepared in the above embodiments and comparative examples with high-transmittance packaging films were tested for component power according to the provisions of 4.10 of IEC61215-2:2016, and the results are shown in Table 1.

[0059] Table 1: Test results of light conversion film performance

[0060] It can be seen from Table 1 that the light-converting adhesive films prepared by the formulation and method of the present invention in Examples 1 to 5 have high transmittance, good UV resistance and long service life.

[0061] In Comparative Example 1, no anti-migration layer is set between the light conversion layer and the UV cutoff layer. The film thickness is low and the film has high transmittance in the visible light region without powder additives. The initial power of the component is high. However, due to the absence of an anti-migration layer, the light conversion agent migrates to the back layer, resulting in serious power loss of the film.

[0062] In Comparative Example 2, the anti-migration layer is not pre-crosslinked by electron beam irradiation, and the anti-migration layer cannot effectively block the migration of the light conversion agent. The power loss of the film is significantly improved compared with that of Example 1.

[0063] The particle size of the inorganic powder used in the anti-migration layer of Comparative Example 3 is too large, resulting in a decrease in the visible light transmittance of the film and low initial power. In addition, the particle size is too large to effectively block the migration of the light conversion agent, resulting in a large power loss of the film.

[0064] In the anti-migration layers of Comparative Examples 4 and 5, excessive addition of inorganic nanopowder and excessive thickness of the anti-migration layers will also lead to a decrease in visible light transmittance and a low initial power.

[0065] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should be included in the scope of the claims of the present invention.

Claims

1. An anti-migration long-life light-converting adhesive film, characterized in that: It includes a light conversion layer, an anti-migration layer and a UV cut-off layer which are laminated in sequence; The raw materials of the light conversion layer include a first base resin and a light conversion agent; The raw materials of the anti-migration layer include a second matrix resin and an inorganic nano powder; the particle size D50 of the inorganic nano powder is 1-200 nm, and the mass of the inorganic nano powder is 0.01-0.5% of the total mass of the anti-migration layer; the thickness of the anti-migration layer is 15-45% of the total thickness of the anti-migration long-life light-converting adhesive film; The migration layer is pre-crosslinked by electron beam irradiation; The raw materials of the UV cut-off layer include a third base resin and an ultraviolet absorber.

2. The anti-migration long-life light-converting adhesive film according to claim 1 is characterized in that: The inorganic nano powder is selected from one or more of nano calcium carbonate, nano magnesium hydroxide, nano silicon dioxide, nano talc, nano wollastonite, nano titanium dioxide, nano barium sulfate, nano kaolin, nano montmorillonite, nano aluminum hydroxide, nano zinc oxide, and nano aluminum oxide.

3. The anti-migration long-life light-converting adhesive film according to claim 1 is characterized in that: The total thickness of the anti-migration long-life light-converting adhesive film is 500-1400 μm; the thickness of the light-converting layer is 200-600 μm; the thickness of the anti-migration layer is 100-200 μm; The thickness of the UV cutoff layer is 200-600 μm.

4. The anti-migration long-life light-converting adhesive film according to claim 1, characterized in that: The mass of the light conversion agent is 0.02-0.6% of the total mass of the light conversion layer; the mass of the ultraviolet absorber is 0.02-1.0% of the total mass of the UV cut-off layer.

5. The anti-migration long-life light-converting adhesive film according to claim 1, characterized in that: The first matrix resin is selected from one or more of POE, EVA, and PVB; the second matrix resin is selected from one or more of EVA, POE, TPO, PVB, and silica gel; and the third matrix resin is selected from one or more of POE, EVA, and PVB.

6. The anti-migration long-life light-converting adhesive film according to claim 1 or 5, characterized in that: The light conversion layer, the anti-migration layer and the UV cut-off layer further include one or more of a cross-linking agent, an auxiliary cross-linking agent, a silane coupling agent, a photoinitiator, an antioxidant and a light stabilizer.

7. A method for preparing the anti-migration long-life light-converting adhesive film according to any one of claims 1 to 6, characterized in that: The steps include: (1) Mixing the raw materials of the anti-migration layer in proportion and casting the mixture to form a film, and cooling and forming the film to obtain the anti-migration layer; (2) pre-crosslinking the obtained anti-migration layer by electron beam irradiation to obtain a pre-crosslinked anti-migration layer; (3) preparing a light conversion layer and a UV cutoff layer by a casting method, and after cooling and forming, laminating the obtained pre-crosslinked anti-migration layer between the light conversion layer and the UV cutoff layer by roller pressing, thereby obtaining the anti-migration long-life light conversion adhesive film.

8. The method for preparing the anti-migration long-life light-converting adhesive film according to claim 7, characterized in that: The pre-crosslinking degree of the pre-crosslinked anti-migration layer obtained in step (2) is 20-80%.

9. The method for preparing the anti-migration long-life light-converting adhesive film according to claim 7, characterized in that: In step (3), the temperature during roller pressing is 50-110°C and the pressure is 0.1-10.0 MPa.

10. An application of the anti-migration long-life light-conversion adhesive film according to any one of claims 1 to 6 in a photovoltaic module, characterized in that: The photovoltaic module comprises a solar cell, and the two sides of the solar cell are respectively adhered with the anti-migration long-life light-conversion adhesive film; the UV cutoff layer of the anti-migration long-life light-conversion adhesive film is adhered to the solar cell.

Citation Information

Patent Citations

  • Light conversion film with double-layer structure and photovoltaic module applying light conversion film

    CN115044325A

  • Photovoltaic adhesive film with light conversion function

    CN116766721A

  • EVA adhesive film, preparation method and application thereof in photovoltaic assembly

    CN106967368A

  • Multi-layer composite photovoltaic packaging adhesive film resistant to PID (potential induced degradation) as well as preparation method and application

    CN109337599A

  • UV light conversion packaging adhesive film and preparation method thereof

    CN114958215A

Cited By

  • PVB resin with light conversion effect and preparation method thereof

    CN120463843A